Islam and the Struggle for Multiculturalism in Singkawang, West Kalimantan: Local Ulama, Theological-Economic Competition and Ethnoreligious Relations - Dwi Surya Atmaja; Fachrurazi Fachrurazi; Lalu Agus Satriawan; Eko Asmanto; Budi Sukardi (Ulumuna, 2023)
This study explores the dynamics of multiculturalism in Singkawang, the most tolerant city in Indonesia. It surprises every scholar studying conflicts as the city can adequately manage conflicts. It was evidenced by the cessation of the deadly conflict, the Sambas 1999 in the city, and by the establishment of ethnocultural groups inherited since the Dutch colonialism that generated pseudo-multiculturalism, in which all ethnic and religious communities have been tolerant but exclusive and fragile to conflict. Fortunately, as the champ of economic but socio-political competition, the Chinese have an ancestral tradition of sharing their wealth considerably. This is with no regard to either the profane or sacred places or their Muslim counterparts' social or ritual activities. Supposedly, instead of refusing "infidelity" contributions, local ulama appreciate and, in return, struggle to promote the substitution of pejorative calls of Chinese with Tionghoa. In conclusion, theoretically, economic welfare is the mayonnaise poured over Singkawang's "Salad Bowls," maintaining its conducive but pseudo-multiculturalism.